Demographics and Clinical Profile of Patients Admitted to a Palliative Care Unit of a Tertiary Cancer Center in Nepal - Wagle, Bhawana; Thapa, Pradeep; Rajbhandari, Ratna; Malla, Ashesh (Nepalese Journal of Cancer, 2025)
Background: Cancer remains a major cause of morbidity and mortality in Nepal, with increasing demand for palliative care services. This study aimed to describe the demographic characteristics, symptom burden, and clinical outcomes of cancer patients admitted to a tertiary cancer center in Nepal.Methods: A descriptive, retrospective review of electronic medical records was conducted for all cancer patients admitted to the PCU of B.P. Koirala Memorial Cancer Hospital, Bharatpur, from July 16, 2024, to July 16, 2025; following ethical approval. Data on demographics, diagnosis, symptoms, length of stay (LOS), and clinical outcomes were extracted and analyzed using descriptive statistics.Results: A total of 170 patients were included, with a median age of 45 years, 59.4% females and highest numbers from Chitwan and Lumbini Province. Lung cancer (11.8%), sarcoma (11.2%), and cervical cancer (10.6%) were the most common diagnoses. Pain was nearly universal (98.8%) with median LOS was 6 days. Clinical outcomes included discharge (49.4%), death (26.5%), discharge on patient request (21.2%), and transfer for active treatment (2.9%).Conclusion: The findings highlight a relatively young median age (45 years), a predominance of female patients, geographic clustering of admissions, lung cancer as leading diagnoses, high levels of symptom burden—especially pain—and mixed outcomes - nearly half discharged and one-fourth dying in the unit; with median LOS of 6 days; underscoring the importance of strengthening palliative care services in Nepal.